Just for future reference always put ^ for exponents. The answer is y-6 though.
(y-4)(y-6) create that trinomial. You can prove that by using the FOIL algorithm
Square root each side
x-5=positive/negative 9
x=14, and -4
(not <em>a</em> or not <em>b</em>) implies <em>c</em> <==> not (not <em>a</em> or not <em>b</em>) or <em>c</em>
so negating gives
not [(not <em>a</em> or not <em>b</em>) implies <em>c</em>] <==> not[ not (not <em>a</em> or not <em>b</em>) or <em>c</em>]
which we can simplify somewhat to
not (not (not <em>a</em> or not <em>b</em>)) and not <em>c</em>
(not <em>a</em> or not <em>b</em>) and not <em>c</em>
(not <em>a</em> and not <em>c</em>) or (not <em>b</em> and not <em>c</em>)
not (<em>a</em> or <em>c</em>) or not (<em>b</em> or <em>c</em>)
not ((<em>a</em> or <em>c</em>) and (<em>b</em> or <em>c</em>))
not ((<em>a</em> and <em>b</em>) or <em>c</em>)
This is going to be 4 remainders one.
Lee's shoe size would be a 9
9 6 6
Range = biggest value - smallest value
9-6 = 3